Student’s awareness about human right / Siti Rubiah Mohd Rusli ... [et al.] - Mohd Rusli, Siti Rubiah; Ikhsan, Nur Izzah; Saaidin, Mohd Syahmie; Yusoff, Ahmad Fathi (2007)
Our research report explains about “student awareness about human right”. We had chosen diploma in public administration and bachelor in administration science as our case study. The method that we use in this research is through observation, research, comparison, news cutting, magazine and internet. We had distributed 100 copies of questionnaire. And the result that we get from that questionnaire will be show in statistic form. Early and systematic step should be taken by the responsible organization in order to give and teach the public’s especially the students about the important of human right. So, they can aware about their right and try to protect it. We hope all the suggestion that we get through this research will bring benefit to all people who involve in.